IDENTIFYING THE TYPES OF STRUGGLE IN SHAWN MENDES SONG’S LYRICS - Wulan Sari, Sulhizah; Situmeang, Ulibasa (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2021)
This study aims to show the type of struggle in the three songs sung by Shawn Mendes. A qualitative descriptive method was used. There are three Shawn Mendes songs discussed in this study; In My Blood, Treat You Better, and Stitches. The analysis results show that there are two kinds of struggles in the song In My Blood; internal and external struggles. The main character overcomes his problems by telling himself never to give up, doing some activities to help himself, trying to calm himself down, and asking someone for help. The title of the song, Treat You Better, has an external struggle and internal struggle. The main character’s struggles are shown by helping the woman he likes, giving his lover everything she wants, and promising his lover that he will never let him down. In the last song, Stitches, there are internal and external struggles. The main character struggles to solve problems by healing his pain, believing that he can survive his pain, and receiving help from someone. The importance of this analysis is to show that the meaning of the lyrics and the story behind the song represents the struggle of the story of human life for surviving and fighting against their problems.